Sphingolipid metabolism during epidermal barrier development in mice - Thomas Doering; Helmut Brade; Konrad Sandhoff (Journal of Lipid Research, 2002)
In rodents, a competent skin barrier to water loss is formed within 2 or 3 days prior to birth. Acquisition of barrier function during rat gestation correlates with the formation of a stratum corneum enriched in ceramides, cholesterol, and fatty acids (Aszterbaum, M., G. K. Menon, K. R. Feingold, and M. L. Williams. 1992. Ontogeny of the epidermal barrier to water loss in the rat: correlation of function with stratum corneum structure and lipid content. Pediatr. Res. 31: 308–317). We analyzed the formation and epidermal localization of glucosylceramides during embryonic skin barrier development in Balb/c mice. Using immunohistochemistry, epidermal glucosylceramides were hardly detectable 3 days prior to birth. After further 24 h of gestation the level of glucosylceramides was maximal and decreased with increasing gestational age. In parallel, glucosylceramides were targeted to the apical side of the outermost granular keratinocyte layer. A spectrum of five distinct epidermal ceramides was present 2 days prior to birth. With ongoing gestation the composition of the ceramide fraction changed markedly. Most importantly, the level of ω-hydroxylated acylceramides decreased paralleled by the formation of the corneocyte lipid envelope. This structure consists of ω-hydroxylated ceramides and fatty acids bound to surface proteins of the corneocytes.The covalent attachment of ceramides or glucosylceramides correlated with the maturation of the stratum corneum and might contribute to its chemical and enzymatic resistance.